A systematic review on~homo~Islamicus: Classification~and critique - Muhammad Sholihin; Catur Sugiyanto; Akhmad Akbar Susamto (Islamic Economic Studies (IES), 2023)
Purpose - This paper aims to systematically review the concept of homo Islamicus discussed in the existing literature. The second objective is to offer a set of criticisms of the descriptions of homo Islamicus. Design/methodology/approach - In this paper prespecified eligibility criteria are applied to select articles that are indexed in Scopus and ProQuest, or published by two major publishers, ScienceDirect and Emerald, or appear on ResearchGate. A set of books related to homo Islamicus was also used as secondary sources to support the selected articles. As a result, this paper systematically reviews 53 articles and four books to synthesize the homo Islamicus. Findings - There are four notions of homo Islamicus: Firstly, homo Islamicus as the kind of economic agent that is required to achieve Islamic economic objectives. Secondly, homo Islamicus as a defining factor that makes the difference between Islamic and conventional economics. Thirdly, homo Islamicus as an economic agent whose characteristics are something Islamic economics aims to realize. Lastly, homo Islamicus as an economic agent representing the fundamental assumption in Islamic economics. Practical implications - Mapping homo Islamicus can be helpful for future researchers to conduct analyses related to homo Islamicus, especially in the context of empirical studies of the existence of homo Islamicus in economic reality. This literature review can help other researchers to understand the development of literature related to homo Islamicus. Originality/value - This paper seems to be the first to systematically identify, select and synthesize the description of homo Islamicus in the literature.
Keywords: B3; B4; 330; Altruism; Homo economicus; Homo Islamicus; Maslahah comparison; Noncognitive factors; Utilitarianism